Prediction of Moral Disengagement and Incivility Against the Honesty of Junior High School Students - Sunawan Sunawan; Anwar Sutoyo; Imam Setyo Nugroho; Susilawati Susilawati (Bulletin of Counseling and Psychotherapy, 2023)
Honesty is a significant issue being investigated in the academic world due to the prevalence of dishonesty such as cheating and plagiarism among students. This research aims to examine the relationship between students' honesty and their moral disengagement and incivility perspectives. A correlational study was conducted with 636 students from two junior high schools in Central Java using cluster sampling. Participants completed the academic integrity scale, moral disengagement scale, and incivility scale. The results indicated that moral disengagement and incivility significantly predict students' honesty, as confirmed by the significant correlation (R = .41, F (13,622) = 9.57, p < .01). The study's results suggest that factors such as euphemistic labeling, dehumanization, unintentional incivility, and intentional incivility contribute to students' honesty. The findings of this study highlight the importance of addressing moral disengagement and incivility in educational settings. To promote honesty and positive behavior among students, educational institutions may consider implementing programs that address these factors and encourage positive moral reasoning and respectful behavior. Further discussion of these results is provided in the study.